2023
DOI: 10.1140/epjd/s10053-023-00688-4
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic N$$_2$$+H$$_2$$ collisions and quantum-classical rate coefficients: large datasets and machine learning predictions

Abstract: Rate coefficients for vibrational energy transfer are calculated for collisions between molecular nitrogen and hydrogen in a wide range of temperature and of initial vibrational states ($$v\le 40$$ v ≤ 40 for N$$_2$$ 2 and $$w\le 10$$ w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The discrepancies in the whole temperature range are however more reliable than those obtained by the first-order theory or by widely employed extrapolation techniques, which might present orders of magnitude differences with the calculated data (see, e.g. , ref ). For the highest v = 54, the rate coefficients are very different both at low (up to 2 orders of magnitude) and high (a factor of 3) temperatures.…”
Section: Effect Of Intramolecular Potential On V–v and V–t/r Rates An...mentioning
confidence: 99%
See 4 more Smart Citations
“…The discrepancies in the whole temperature range are however more reliable than those obtained by the first-order theory or by widely employed extrapolation techniques, which might present orders of magnitude differences with the calculated data (see, e.g. , ref ). For the highest v = 54, the rate coefficients are very different both at low (up to 2 orders of magnitude) and high (a factor of 3) temperatures.…”
Section: Effect Of Intramolecular Potential On V–v and V–t/r Rates An...mentioning
confidence: 99%
“…The same settings employed in ref 21 are adopted: a Matern kernel where an extra parameter (i.e., ν, taken here equal to 5/2) in the covariance function is used to specify the smoothness of the resulting function. We employed the GPR approach as implemented in scikit-learn 52 (the code is freely available at ref 53), as recently done in ref 13, where we compared the performance of two different machine learning techniques (i.e., GPR and artificial neural network) to predict rate coefficients for the inelastic scattering collisions between N 2 and H 2 . It is found that, as far as interpolation is concerned, i.e., the v values for which rates are predicted fall within the interval of calculated v, GPR is able to perform very well in terms of test set mean squared error (MSE) values.…”
Section: V−v and V−t/r Complete Data Sets By Gprmentioning
confidence: 99%
See 3 more Smart Citations